User needs analysis for a children,s library in barangay UP campus - Kalngan, Michael Lloyd J. (2007)
The study is concerned with the perceptions of Barangay UP Campus community towards the user needs in a children's library in their respective area. A user needs analysis was carried out to determine the answers to this study's main objectives of: (1) finding out the socio-demographic profile of Barangay UP Campus; (2) verifying the perceived user need of children by the members of the community; and (3) establishing the overall view of the community towards establishing a children's library in the barangay.